Health promotion and education in Portuguese schools: links between the health and the education sectors - Lusquinhos, Leonel (2017)
The purpose of the study is to analyse the links between the health and the education sectors in legal documents and in field practices, i.e., to compare the theory with the practice of implementing health promotion and education programmes in schools. In a first phase, a document analysis study on the organization of health services and education services regarding, respectively, the "School Health" and "Health Education" national programmes and guidelines was carried out in order to understand the contributions of both sectors to the health promotion and education in schools. A second phase will be carried out in the field by assessing the implementation processes of health promotion and education programmes in schools. The preliminary analysis of key documents has showed that the partnership between Health and Education sectors exists formally since 1994, when Portugal joined the European Network of Health Promoting Schools (ENHPS). Later, in 2006, both Ministries of Health and Education signed a common protocol for the development of health promotion and education activities. The commitments assumed by both sectors aim at promoting active participation and interdisciplinary team of health and education professionals in order to build a common and structured health promotion and education programme with the contribution of different areas of knowledge (health and education). Both Ministries have developed measures and undergone structural changes that allow a deeper and more systematic cooperation between health and education sectors. Taking into account the documents produced by the Ministries of Health and Education, it can be concluded that the foundations for a successful interaction between these two sectors have been set up. Future work in the field, by assessing the implementation processes of health promotion and education programmes in schools, will show how the practices incorporate the theory.